The Effect of Gamified Teamwork on Business-related Idea Generation - Polina Trusova (Journal of Games, Game Art, and Gamification, 2018)
Innovation providing a competitive advantage to enterprises is based on original ideas usually developed by teams. Therefore, the optimization of idea generation in teams is crucial for the enterprises’ competitiveness and survival. The goal of this experimental study is to test whether idea generation in team can be made more effective in terms of quantity and quality through gamification (the use of game design elements in non-game contexts). Based on conservation of resources theory, in the present study gamification was assumed to generate and regulate task-related resources and therefore to increase the number and originality of generated ideas. 170 students divided in 70 teams were asked to imagine themselves to be a management team of a young innovative enterprise during a crisis meeting and to generate solutions for the described problems. 35 teams were randomly assigned to the gamification condition and another 35 teams to the control condition. The number and originality of ideas were evaluated by two independent condition-blind raters and compared between the conditions. Gamification has a large positive effect on the idea number and a medium-sized positive effect on the idea originality. The findings, implications and limitations are discussed.